India's Services Sector Growth : The Impact of Services Trade on Non-tradable Services - Avdiu, Besart; Bagavathinathan, Karan Singh; Chaurey, Ritam; Nayyar, Gaurav (World Bank, Washington, DC, 2022)
This paper examines the effect of tradable services growth on non-tradable services across Indian districts. The analysis uses a shift-share “Bartik-type” instrumental variable, which relies on changes in foreign demand shocks for tradable services, weighted by the initial district employment shares in tradable services. Using multiple rounds of the Indian Economic Censuses, the findings show that an increase in tradable services employment leads to an increase in non-tradable services employment and increases the number of firms in non-tradable services. The evidence suggests that this positive impact is due to an increase in consumer demand for local non-tradable services that results from the growth in tradable services employment, and not due to sectoral linkages between tradable and non-tradable services sectors. The employment impact is much larger for female workers compared to male workers, and for the number of female-owned firms relative to male-owned firms. Further, the employment impact is only significant for small non-tradable service firms.